Clinical Evidence in the Treatment of Obstructive Sleep Apnoea with Oral Appliances: A Systematic Review - Andrea Rossi; Antonino Lo Giudice; Camilla Di Pardo; Alberto Teodoro Valentini; Francesca Marradi; Nicola Vanacore; Cristina Grippaudo (International Journal of Dentistry)
Background. Recent clinical guidelines have extended indications for oral appliances to subjects affected by moderate-to-severe obstructive sleep apnoea (OSA). The aim of this systematic review covering this important issue for public health is twofold: updating and summarizing the best available scientific evidence by selecting RCTs of quality only, and identifying the therapeutic pathways that can be transferred to the current clinical practice. Methods. All the abstracts which were published before February 18, 2019, have been identified in three electronic databases (PubMed, Web of Science, and Cochrane). The Cochrane Collaboration’s tool for assessing risk of bias was used as an assessment tool in order to evaluate the quality of the selected studies. Results. The search strategy yielded 2,260 studies. After removing duplicates and studies that did not comply with the inclusion criteria, 32 full-text articles were assessed for eligibility, and 17 RCTs were finally included in the qualitative synthesis. The 17 selected studies were very heterogeneous in the type of included RCTs in terms of patient inclusion criteria, sample size, distribution of the two genders in the various groups, duration of treatment, and definition of primary and secondary outcomes, without any restriction on the definition of the control group. A common finding was the positive responsiveness of oral appliance treatment in subjects affected by mild-to-moderate OSA with some evidence for cases of severe OSA. Conclusion. Higher-quality studies are needed in order to provide additional useful guidelines for dental clinicians for OSA management.